(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2014)
This position paper uses the earth smarts framework as a basis to argue that a set of community-based skills, attuned to global and local contexts, have become important aspects of both scientific and environmental education. Regardless of where you live in the world, working together effectively is more important than ever, particularly on scales beyond our immediate families and local communities. Modern democracies require citizens that can manage multiple perspectives, communicate and collaborate in an increasingly connected world, resolve conflicts less violently, and navigate issues that often involve different and conflicting values. As the scale of the environmental challenges we face has become global, the solutions to many of them are beyond the scope of any individual or small group. In this context the themes of this issue, democracy, citizenship, and social justice, can be seen not simply as educational goals, but rather as tools to help us achieve more just, resilient communities in the face of accelerated environmental change.